Effect of bovine leukemia virus infection on bovine peripheral blood monocyte responsiveness to lipopolysaccharide stimulation in vitro - Werling, D.; Sileghem, M.R.; Lotz, H.; Langhans, W. (Elsevier, 1995)
The effects of bovine leukemia virus (BLV) infection on cytokine activity of bovine monocytes simulated with Escherichia coli lipopolysaccharide (LPS) were examined. Compared to supernatants of LPS-simulated monocytes from BLV-negative cows, supernatants from BLV-positive cows contained about four times more interleukin-1B(IL-1B) (as measured by an enzyme-linked immunosorbent assay (ELISA) for bovine IL-1B). Despite their higher IL-1B concentration, supernatants from BLV-positive cows stimulated proliferation of murine thymocytes in the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-biphenyl tetrazolium bromide) assay similar to supernatants from BLV-negative cows, but showed about 30 percent less IL-1 activity than supernatants from BLV-negative cows on the IL-1-dependent cell line LBRM-33 1 A-5, and about five times more tumor necrosis factor (TNF) activity on the TNF-sensitive murine fibroblast cell line L-929. These results demonstrate that BLV infection changes the cytokine response of bovine monocytes to LPS simulation in vitro. The results are consistent with the assumption that BLV infection leads to the production and secretion of a soluble IL-1 inhibitor by LPS-simulated peripheral blood monocytes.